Preservation of stewed beef chunks by using ϵ-polylysine and tea polyphenols. (July 2021) - Li, Fuhou; Wu, Shengjun; Xu, Bing
Abstract: Tea polyphenols and ϵ-polylysine have antibacterial activities, and tea polyphenols have antioxidant activity. In this study, the combination of ϵ-polylysine and tea polyphenols was used to preserve stewed beef chunks during room-temperature storage. The beef chunks stewed in the broth containing 0.02% ϵ-polylysine and 0.02% tea polyphenols exhibited no change in bacterial growth, pH, total volatile basic nitrogen (TVB-N) and thiobarbituric acid-reactive substance (TBARS) contents and sensory quality during room-temperature storage for 12 days. The beef chunks stewed in the control broth had significant increases in bacterial growth, pH, TVB-N content and TBARS content by 220% (P < 0.05, based on log colony-forming unit/g), 40% (P < 0.05), 239% (P < 0.05) and 153% (P < 0.05), respectively, and a significant decrease in sensory quality by 46% (P < 0.05) after 12 days of room-temperature storage. Results indicated that the combination of ϵ-polylysine and tea polyphenols could be a promising method to preserve stewed beef chunks during room-temperature storage. Highlights: ϵ-polylysine and tea polyphenols suppressed bacterial growth in stewed beef. ϵ-polylysine and tea polyphenols inhibited pH increase in stewed beef. ϵ-polylysine and tea polyphenols suppressed TVB-N increase in stewed beef. ϵ-polylysine and tea polyphenols maintained sensory quality of stewed beef.